A comprehensive safety profile of tafamidis in patients with transthyretin amyloid polyneuropathy. (2nd October 2019) - Huber, Peter; Flynn, Alison; Sultan, Marla B.; Li, Huihua; Rill, Denise; Ebede, Ben; Gundapaneni, Balarama; Schwartz, Jeffrey H.
Abstract: Background: Tafamidis is approved in over 40 countries to delay neurologic progression in patients with transthyretin amyloid polyneuropathy (ATTR-PN). A comprehensive, integrated analysis of safety data from interventional, observational and surveillance studies of tafamidis in ATTR-PN patients was conducted. Methods: Safety data from all sponsored, completed, or ongoing, Phase 2/3 studies of tafamidis in ATTR-PN patients as of 3 January 2017 were pooled. Also assessed were safety data from the ongoing Transthyretin Amyloidosis Outcomes Survey (THAOS) as of 3 January 2017 and post-marketing surveillance reports as of 31 March 2017. Results: There were 137 patients in Phase 2/3 studies (mean duration of tafamidis exposure, 44.2 months), with 134 (97.8%) experiencing ≥1 treatment-emergent adverse event (TEAE) and 46 (33.6%) ≥1 treatment-emergent serious adverse event (TESAE). The most common TEAEs were diarrhoea (26.3%), urinary tract infection (UTI; 25.5%) and influenza (21.2%). In THAOS, 661 subjects had tafamidis exposure (mean duration, 27.6 months), with 250 (37.8%) experiencing ≥1 TEAE and 96 (14.5%) ≥1 TESAE. The most common TEAE was UTI (6.1%). Post-marketing surveillance reports generally reflected the known safety profile of tafamidis. Conclusions: This analysis did not reveal any significant new safety findings; tafamidis was generally safe and well tolerated in ATTR-PN patients. Trial registration: ClinicalTrials.gov identifier: NCT00409175. Trial registration: ClinicalTrials.gov identifier: NCT00791492. Trial registration: ClinicalTrials.gov identifier: NCT00630864. Trial registration: ClinicalTrials.gov identifier: NCT01435655. Trial registration: ClinicalTrials.gov identifier: NCT00925002. Trial registration: ClinicalTrials.gov identifier: NCT00628745.